COMPARATIVE STUDY OF METRONIDAZOLE AND RIFAXIMIN IN PATIENTS WITH HEPATIC ENCEPHALOPATHY - AZHAR , S; AHMED , SI; MUKHTAR , A; AZHAR , H; HASSAN , A; HASHIR , Z (Biological and Clinical Sciences Research Journal, 2023)
Hepatic encephalopathy (HE) is a complex neuropsychiatric syndrome due to liver brokenness, especially in patients with cirrhosis or intense liver failure. The study's main objective is to find the comparative effectiveness of metronidazole and rifaximin in patients with hepatic encephalopathy. This prospective comparative study was conducted at Islamabad Medical and Dental College, Islamabad, over six months, from January 2023 to July 2023. The study population consisted of adult patients (age 18 years and above) diagnosed with hepatic encephalopathy admitted to the hospital's medical wards or gastroenterology department during the study duration. Patients with a confirmed diagnosis of hepatic encephalopathy based on clinical and laboratory criteria were included in the study. Out of the 150 patients enrolled in the study, 75 were randomized to receive metronidazole (Group A) and 75 to receive rifaximin (Group B). All patients completed the 10-day treatment period, and there were no dropouts during the study. In Group A (metronidazole), 60 out of 75 patients (80%) showed improvement in hepatic encephalopathy based on the West Haven criteria. In Group B (rifaximin), 70 out of 75 patients (93.33%) showed improvement in hepatic encephalopathy based on the West Haven criteria. The improvement in hepatic encephalopathy was significantly higher in Group B (rifaximin) compared to Group A (metronidazole) (p < 0.05).